Assessment of organizational effectiveness: a comparative study in between public and private sector - Vijayakumar; Nawaz, Nishad; Tharanya (International Journal of Psychosocial Rehabilitation, 2020)
The present has been aim to assessment of organizational effectiveness among the banks of public and private, which are located in the area of Chennai, India. The data collected by using primary data with structured questionnaire among the employees of scale I, and scale-II officers) in selected banks. The convenience sampling was adopted collected 100 samples from each bank put together 400 samples were cumulated from the selected Banks namely State Bank of India, Punjab National Bank, public sector and another two from private sector banks i.e ICICI Bank and HDFC Bank. After analyzing of the collected data, the results indicate that the organizational effectiveness significantly differs in public and private sector banks. The study also reveals that there is no important disparity among public and private sector banks concerning the organizational effectiveness in the study region. Both the sectors of banks are properly managing the employee engagement and performance